Management of wet AMD in an elderly patient - case report - Katarzyna Nowakowska; Przemyslaw Raczkiewicz; Martyna Lewkowicz; Karolina Raksa; Karolina Urbańska (Kazimierz Wielki University, 2021)
Introduction: Age-related macular degeneration (AMD) is the most common cause of central vision loss in elderly people over 50 years of age. It is characterized by the presence of drusen on the fundus and may be associated with choroidal neovascularization (CNV) or geographic atrophy. AMD is a condition caused by many factors including environmental, genetic, and vascular. Currently, it affects over 25 million people worldwide, but with the progressive aging of the population, the incidence of the disease is increasing. Disease is therefore an important issue in geriatrics. Case report: A 75-year-old patient was referred to the General and Pediatric Ophthalmology Clinic of the Medical University of Lublin due to the three-week deterioration of visual acuity in the left eye. The visual acuity of the left eye was: counting fingers at a distance of 1.5 m. Initial cataracts of this eye and wet AMD were diagnosed. In July 2018. an injection of ranibizumab was administered into the vitreous humor of the left eye. After achieving an improvement in visual acuity to 0.2 (on Snellen charts), in September the patient was qualified to the Drug Program for the treatment of the wet form of AMD. From September to October 2019. the patient received 9 doses of ranibizumab. In October 2019. visual acuity improved to 0.4. In November, due to the unsatisfactory results of the therapy, the drug was changed to aflibercept. The patient received a total of 3 injections of this drug and his visual acuity improved to a value of 0.7. The last injection was given in July 2020 and the clinical condition and visual acuity stabilized. After the end of the drug program, the patient regularly shows up for checkups, and the visual acuity of the left eye has normalized since July 2020. and is now 0.4 (due in part to atrophic changes and scarring). Conclusions: Treatment of the wet form of AMD is a difficult and lengthy process. Early diagnosis of the disease, starting treatment as soon as possible, regular checkups and cooperation with the patient are very important for the success of the therapy. During 3 years of treatment, the patient experienced a significant improvement in visual acuity for one year. The treatment allowed the disease progression to slow down. The morphological condition of the retina improved. The applied treatment and management of the elderly patient turned out to be effective, and the achieved effects of the therapy are satisfactory.